2020
DOI: 10.3389/fpsyt.2020.00176
|View full text |Cite
|
Sign up to set email alerts
|

Neural Bases of Cognitive Impairments in Post-Traumatic Stress Disorders: A Mini-Review of Functional Magnetic Resonance Imaging Findings

Abstract: Introduction: Post-Traumatic Stress Disorder (PTSD) is often associated with impairments in emotional and cognitive domains. Contrarily to the emotional sphere, neural basis underpinnings to cognitive impairments are still not well known. Methods: We performed a bibliographic search on PUBMED of all the studies investigating the cognitive impairments in PTSD individuals. We considered only studies that applied cognitive tasks using a functional Magnetic Resonance Imaging technique. The inclusion criteria were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Chronic PTSD may influence several key brain structures, including the hippocampus, which has been found to be smaller in PTSD due to the effects of chronic stress. Changes like these, in turn, may influence baseline autonomic activity and its reactivity to stress (Dossi et al, 2020). The associations of acute PTSD symptoms with DC and LF HRV emphasize the importance of particular structures involved in parasympathetic function (DC), such as the nucleus ambiguus and the dorsal vagal nucleus, as well as the baroreflexes, like the insular cortex, anterior cingulate cortex, medial prefrontal cortex, amygdala and cerebellum (Kimmerly, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic PTSD may influence several key brain structures, including the hippocampus, which has been found to be smaller in PTSD due to the effects of chronic stress. Changes like these, in turn, may influence baseline autonomic activity and its reactivity to stress (Dossi et al, 2020). The associations of acute PTSD symptoms with DC and LF HRV emphasize the importance of particular structures involved in parasympathetic function (DC), such as the nucleus ambiguus and the dorsal vagal nucleus, as well as the baroreflexes, like the insular cortex, anterior cingulate cortex, medial prefrontal cortex, amygdala and cerebellum (Kimmerly, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PTSD had higher functional connectivity between the dACC with regions in the sensorimotor network in comparison to trauma-exposed and healthy controls, which may be related to preparing for the fight or flight response. On the other hand, patients with PTSD showed decreased functional connectivity between the dACC with the bilateral middle frontal gyrus and inferior frontal gyrus -areas important for response inhibition (Dossi, Delvecchio, Prunas, Soares, & Brambilla, 2020) -compared to individuals who were also exposed to trauma but did not develop PTSD. In addition, decreased functional connectivity between the dACC with the right hippocampus was found for both trauma-exposed groups but was more severe in the PTSD group.…”
Section: Pathophysiologymentioning
confidence: 99%
“…In the years after 9/11, approximately 23% of these responders continued reported symptoms of chronic post-traumatic stress disorder [PTSD] [ 1 , 22 , 23 ]. Several studies by our group [ 2 , 3 , 24 , 25 ] and other investigators [ 26 29 ] have shown that PTSD is a risk factor for cognitive impairment (CI). Neuroimaging studies have identified neurobiological changes in the brains of patients with PTSD [ 30 ].…”
Section: Introductionmentioning
confidence: 99%